CAS directly interacts with vinculin to control mechanosensing and focal adhesion dynamics - Janoštiak, Radoslav; Brábek, Jan; Auernheimer, Vera; Tatárová, Zuzana; Lautscham, Lena A; Dey, Tuli; Gemperle, Jakub; Merkel, Rudolf; Goldmann, Wolfgang H; Fabry, Ben; Rösel, Daniel (Cellular and molecular life sciences, 2014)
Focal adhesions are cellular structures through which both mechanical forces and regulatory signals are transmitted. Two focal adhesion-associated proteins, Crk-associated substrate (CAS) and vinculin, were both independently shown to be crucial for the ability of cells to transmit mechanical forces and to regulate cytoskeletal tension. Here, we identify a novel, direct binding interaction between CAS and vinculin. This interaction is mediated by the CAS SRC homology 3 domain and a proline-rich sequence in the hinge region of vinculin. We show that CAS localization in focal adhesions is partially dependent on vinculin, and that CAS-vinculin coupling is required for stretch-induced activation of CAS at the Y410 phosphorylation site. Moreover, CAS-vinculin binding significantly affects the dynamics of CAS and vinculin within focal adhesions as well as the size of focal adhesions. Finally, disruption of CAS binding to vinculin reduces cell stiffness and traction force generation. Taken together, these findings strongly implicate a crucial role of CAS-vinculin interaction in mechanosensing and focal adhesion dynamics.
Keywords: Fibroblasts; Phosphorylation; src Homology Domains; src homologní domény; fokální adhezní tyrosinkinasy; fosforylace; Vinculin; Protein Binding; Focal Adhesions; Crk-Associated Substrate Protein; Cell Adhesion; zvířata; Focal Adhesion Protein-Tyrosine Kinases; myši; peptidy; Mice; Peptides; buněčné linie; Cell Line; mapy interakcí proteinů; vinkulin; vazba proteinů; aminokyselinové motivy; fibroblasty; Animals; buněčná adheze; biomechanika; fokální adheze; Amino Acid Motifs; Biomechanical Phenomena; Protein Interaction Maps; substrátový protein asociovaný s Crk